2020
DOI: 10.3329/bjm.v36i2.45537
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antibiotics: Anti-Bacterial Activity or Microbial Drug Resistance?

Abstract: Antibiotics, both broad- and narrow spectrum, are widely used for treatment of specific infection by a consortium of microorganisms or by a single pathogen, respectively. Oral or intravenous, or even topical administration of different categories of antibiotics in various forms is a common practice round the globe. Yet for the recent years a major public health issue has been raised by the emergence of the drug-resistance microorganisms. A number of researches focused on the issue of the ineffectiveness of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The excessive use of antimicrobial drugs has contributed to the development of antimicrobial resistance, which is currently considered a major public health problem. While antimicrobial resistance can occur as a spontaneous phenomenon, evidence has demonstrated that the inappropriate exposure to drugs such as antibiotics and antifungals is contributing to the selection of resistant microorganisms (Sekyere and Asante, 2018;Noor et al, 2019;Hutchings et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The excessive use of antimicrobial drugs has contributed to the development of antimicrobial resistance, which is currently considered a major public health problem. While antimicrobial resistance can occur as a spontaneous phenomenon, evidence has demonstrated that the inappropriate exposure to drugs such as antibiotics and antifungals is contributing to the selection of resistant microorganisms (Sekyere and Asante, 2018;Noor et al, 2019;Hutchings et al, 2019).…”
Section: Introductionmentioning
confidence: 99%